Critical Connections : Promoting Economic Growth and Resilience in Europe and Central Asia - Gould, David Michael (Washington, DC: World Bank, 2018)
Critical Connections examines how trade, investment, migration, and other linkages among countries drive economic growth in the Europe and Central Asia region. The study breaks new ground by using a multidimensional approach that recognizes how each connectivity channel for growth is likely to be affected by the strength of other channels. This multidimensional view makes it easier to see that diversity in country connections and balance in all channels of connectivity are critical for achieving the greatest impact on growth.